ANALYSIS OF THE EFFECT CORPORATE GOVERNANCE AND COMPANY CHARACTERISTICS ON ACCOUNTING CONSERVATISM IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Widijaya Widijaya; Vivian Vivian (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The study was conducted to examine and analyze the effect of the independent variable, namely corporate governance and company characteristics on the dependent variable, namely accounting conservatism. The independent variables of corporate governance consist of the size of the board of directors, independent board of directors, type of auditor and the independent variables of company characteristics consist of firm size, leverage, profitability, and sales growth. Measurement of accounting conservatism in this research is measured based on accrual-based following Al-Saidi (2020). The object of this research are companies that have annual reports that are registered and published on the Indonesia Stock Exchange. The data used in this research was 5 years for the period from 2016 to 2020. There are 729 companies listed on the Indonesia Stock Exchange, only 436 companies passed the selection to be used in this study. The data that has been collected will be processed using SPSS software and Eviews which will be analyzed using a panel regression model. The results obtained by the researcher indicate that the independent board of directors, leverage, profitability and sales growth have a significant positive effect on accounting conservatism. The variable size of the board of directors, type of auditor and firm size did not show a significant effect on accounting conservatism.